The Mediating Role of Artificial Intelligence on the Relationship between Organizational Climate and Employee Creativity Behavior: A Field Study - Alagele , Hussain K. Hussain; Neama , Nagham H.; alkaseer, Natalya ahmed; Al Dulaimi, Haidar Ali; Abd, Sanaa Eesee (Journal of Ecohumanism, 2025)
The transportation sector is considered one of the important sectors in all countries because of its importance in keeping pace with the development and technology used in various fields. Today, the world competes to provide the best services to customers and citizens. The transportation sector is divided in all countries. In light of the technology used today by some countries, it is considered a qualitative addition to the transportation sector. In this study, three main variables were taken (organizational climate, artificial intelligence, Employee creativity Behavior). A random sample of workers in the transportation sector was taken using a questionnaire as a main tool in collecting data. 220 transport sector workers were selected. The data collected was analyzed through the SPSS statistical program, Model 24, and through the structural equation model, SEM - AMOS program, Model 24. The results showed that the role of the mediator, artificial intelligence, is very important in mediating the relationship between the organizational climate and Employee creativity Behavior. In addition, artificial intelligence affects Employee creativity Behavior, and the organizational climate affects artificial intelligence and innovation directly and indirectly with a positive statistical significance.